Pregnancy and Susceptibility to Infectious Diseases - Elisabeth Sappenfield; Denise J. Jamieson; Athena P. Kourtis (Hindawi Limited, 2013)
To summarize the literature regarding susceptibility of pregnant women to infectious diseases and severity of resulting disease, we conducted a review using a PubMed search and other strategies. Studies were included if they reported information on infection risk or disease outcome in pregnant women. In all, 1454 abstracts were reviewed, and a total of 85 studies were included. Data were extracted regarding number of cases in pregnant women, rates of infection, risk factors for disease severity or complications, and maternal outcomes. The evidence indicates that pregnancy is associated with increased severity of some infectious diseases, such as influenza, malaria, hepatitis E, and herpes simplex virus (HSV) infection (risk for dissemination/hepatitis); there is also some evidence for increased severity of measles and smallpox. Disease severity seems higher with advanced pregnancy. Pregnant women may be more susceptible to acquisition of malaria, HIV infection, and listeriosis, although the evidence is limited. These results reinforce the importance of infection prevention as well as of early identification and treatment of suspected influenza, malaria, hepatitis E, and HSV disease during pregnancy.